Roles of Magelang Alms Agency in Tasharruf Process of Alms, Infaq and Shadaqah From Muzakki - Yasnanto Yasnanto; Nur Rofiq (Jurnal Iqtisad, 2019)
Abstract Paying alms is the third pillars of Islam. The aim of this research are to find out about any roles, contributing factors and the supporting actions to Magelang alms agency by the local government in the- tasharruf process of alms, infaq and shodaqoh from muzakki. Qualitative method is used in this research paper. Researcher found that income until December 31st, 2018 is Rp 2.271.923.817, from the balance in 2017 is Rp 620.996.267 Tasharruf process by December 31st is Rp 1.771.560.305 to the amil people Rp 241.531.855 and Rp 1.530.028.450 for the asnaf. Moreover, the balance by December 31st, 2018 is Rp 500.363.512. Income by June 30th, 2019 is Rp 1.315.059.636 from the balance by 2018 is Rp 500.363.512 and DSKL Rp 814.696.124. Then, tasharruf process by June 30th, 2019 to asnaf and activities program Rp 780.098.400. Finally, the balance by June 30th, 2019 is Rp 534.961.236. The contributing factors of that conditions are lack of awareness of moslem in paying alms by individuals or in groups. Local government have given great support to facilitate physically and non-physically.